Efektivitas Pengelolaan Dana Kelurahan Dalam Mewujudkan Good Governance Pada Kelurahan Sei Rengas Permata Kecamatan Medan Area Kota Medan - Muhammad Ikhsan Fadillah; Masta Sembiring (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
In the sub-dictrict Sei Rengas Permata area, kelurahan funds are used for community development and empowerment. In fact, development in the Sei Rengas Permata Village Area has not yet seen its maximum. From the results of the activities carried out in the Sei Rengas Permata Village, it was found that problems arose in the management of the urban village budget, especially in infrastructure development, whose achievements were only seen to be still below 50%. And in the community empowerment budget classification section, it is necessary to have activities that are more useful and do not cost too much money. Giving funds to the sub-district is so large that there needs to be a big responsibility for the sub-district government. Therefore, the sub-district government must be able to apply planning principles appropriately in accordance with Permendagri Number 130 of 2018 concerning planning, implementation, administration, reporting and accountability. In this study, the type of research that will be used is descriptive research method with a qualitative approach and uses a purposive sampling technique which aims to find out how social interaction occurs. Data collection techniques in this study used interview, observation, and documentation techniques. As for the process of data analysis techniques carried out in qualitative research, namely data collection, data reduction and drawing conclusions. Based on the results of research and discussion it can be concluded that the level of achievement of program results has not been effective. However, in the management of village funds in the Sei Rengas Permata Village, management has been carried out in accordance with the principles of good governance such as transparency, accountability, and participation. Keywords: Village Fund Management, Good Governance